APLIKASI METODE BEDA HINGGA PADA PERSAMAAN SCHRODINGER MENGGUNAKAN MATLAB - odaligo ziduhu lombu (Saintia Fisika, 2013)
The application of finete difference methods to Schrödinger equation in particles for potensial barier uses numerical approach converting finete difference methods into Schrödinger equation, therefor Schrödinger equation will be converted into a discrit form and will be formulated into computer programme using Matlab (Matrix Laboratory) programme language. The result of the computer programme is visualization. The visualization of Schrödinger equation for the potensial barier using software a Matlab with the potensial barier constant according for field L, make a hiperbolic wave (E < V) for field x > 0, and stand wave deBroglie (E > V). Keyword : Wave Schrödinger, Finete Difference Methods, Matlab, Potensial Barier.